Big data governance and perspectives in knowledge management - Strydom, Sheryl Kruger, 1959-; Strydom, Moses, 1944- (Advances in knowledge acquisition, transfer, and management (AKATM) book series., 2019)
"This book explores the complex value and governance issues that arise as a consequence of the big data phenomenon and provides examples of best practices found in organizations concerning teaching and learning in academia and the business-industrial environment. It also investigates improving the profitability and success of different enterprises"--